STRATEGI LANGSUNG KESANTUNAN TINDAK DIREKTIF GURU TAMAN KANAK-KANAK - Ulfah, Anisa (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2020)
The kindergarten students tend to learn by imitating people behavior and language hence the teacher itself must use polite and understandable language as stated in the standard academic qualifications and competence for kindergarten teacher. Politeness in language is closely related to the social norm in particular society. Thus the goal of this research is to describe a teachers’ direct politeness in kindergarten that focus on politeness strategy function of politeness. This study used qualitatif method in the form of language research by using socio pragmatics. In collecting the data, the researcher was an observer. The data of this research was in the form of data form, strategy and the teacher’s function in direct politeness accompanied by recording session in the learning activities in the class. According to data analysis, it was found a description politeness in kindergarden teacher that was explained in politeness strategy covered (1) direct strategy without politeness and (2) direct strategy with politeness covered. Based on the findings, the reseacher makes a conclusions is the use of direct strategy often regarded as less polite is often used by the teacher due to increase learning interaction.